KADAR TRIGLISERID TIKUS PUTIH SETELAH PEMBERIAN BERBAGAI KADAR VCO DAN OLIVE OIL - Yuniwarti, Enny Yusuf Wachidah (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
This research aimed to determine differences in Â triglyceride levels after feeding saturated fatty acid and unsaturated fatty acid. Elevated level of triglycerides can lead to cardiovascular disease.This research used 25 white rat. The method applied was Completely Randomized Design in which the factor was five levels of VCO and Olive Oil namely P1, P2, P3, P4 and P5. P1was the control group, P2 was a group with 5 mL VCO/kg feed. P3 was a group with 10 mL VCO/kg feed. P4 was a group with 5 mL Olive Oil/kg feed. P5 was a group with 10 mL Olive Oil/kg feed.Â Each group repeated five times. Feed and water were given ad libitum for four weeks. The result showed that there was no significant between treatments. Â Keywords : white rat, triglyceride level, olive oil, VCO